PENGELOLAAN DANA FILANTROPI UNTUK PEMBERDAYAAN PENDIDIKAN ANAK DHUAFA (STUDI KASUS PADA BMH CABANG MALANG JAWA TIMUR) - Nasrullah, Aan (State Institute of Islamic Studies (IAIN) Palu, 2015)
This study aims to look at how the Institute of Baitul Mal Hidayatullah (BMH) branch Malang manage and distribute philanthropy funds (zakat, infaq, á¹£adaqah and waqf), for the empowerment of poor children education . The approach in this research is qualitative approach, the research design is case study. The results of this study indicate that philanthropy funds have been collected by BMH Branch Malang will be distributed to the four main programs these are, Propagation Program, Education, Social and Economic. The management of philanthropy funds for poor children's education empowerment distributed on three programs: Berpadu (Beasiswa Peduli Anak Dhuafa), PPAS (Pusat Pengembangan Pendidikan Anak Sholeh), and PSD (Pengembangan Sekolah Dhuafa).